Diagnosis of compliance of health care product processing in Primary Health Care - Camila Eugenia Roseira; Darlyani Mariano da Silva; Isis Pienta Batista Dias Passos; Fabiana Souza Orlandi; Maria Clara Padoveze; Rosely Moralez de Figueiredo
ABSTRACT Objective: identify the compliance of health care product processing in Primary Health Care and assess possible differences in the compliance among the services characterized as Primary Health Care Service and Family Health Service. Method: quantitative, observational, descriptive and inferential study with the application of structure, process and outcome indicators of the health care product processing at ten services in an interior city of the State of São Paulo - Brazil. Results: for all indicators, the compliance indices were inferior to the ideal levels. No statistically significant difference was found in the indicators between the two types of services investigated. The health care product cleaning indicators obtained the lowest compliance index, while the indicator technical-operational resources for the preparation, conditioning, disinfection/sterilization, storage and distribution of health care products obtained the best index. Conclusion: the diagnosis of compliance of health care product processing at the services assessed indicates that the quality of the process is jeopardized, as no results close to ideal levels were obtained at any service. In addition, no statistically significant difference in these indicators was found between the two types of services studied.